Electric vehicles in smart grid: a survey on charging load modelling. Issue 1 (15th February 2019) - Xiang, Yue; Hu, Shuai; Liu, Youbo; Zhang, Xin; Liu, Junyong
Abstract : Electric vehicles (EVs) have been rapidly developed during the last few years due to the low‐carbon industry and smart grid initiatives. Meanwhile, the impact of large‐scale EVs' integration on the reliability and safety of power grids is becoming increasingly prominent. To address and solve these problems, challenges on EV charging control have been presented. Besides, the EV charging load modelling with improved accuracy and rationality is required. To investigate the influencing factors of EV charging load, this survey summarises the existing EV charging load modelling methods. In addition, a new research framework for a scale EV evolution model of charging load is proposed, with an emphasis on reducing the deficiencies of the existing research in dealing with the EV scale development. Moreover, the future research prospect of EV charging load modelling on power system planning, operation, and market design has also been discussed.